Counter Hegemony Through The Role Of The Wasathiyah Millennial Muslim Generation In Realizing World Peace - Bekti Taufiq Ari Nugroho; Eko Susilowati; Bety Rosidah (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
The research findings indicate that the state's authority over society's intellectual life is entirely pursued through cultural mechanisms. This allows the state to establish jurisdiction authority acquired through legitimate means, such as a public decision to accept or reject a policy decision made by a power holder without resorting to Dominio, which is a form of dominance based on violence. In terms of the millennial wasathiyah Muslim generation's role and attempts to bring about peace, the paradigm is the realization of a pluralistic society made up of people from various ethnic, cultural, religious, and other backgrounds who share the same resolve and goals to establish the country and state.